2017
DOI: 10.1002/ep.12691
|View full text |Cite
|
Sign up to set email alerts
|

Consolidated bioprocessing for biofuel‐ethanol production from pine needle biomass

Abstract: Lignocellulosic‐bioethanol‐fuel (LBF) technology faces challenges due to cost/energy intensive nature of lignocellulosic biomass (LB) pretreatment and saccharification. Ionic liquid (IL) based pretreatment of LB has recently emerged as an environmentally friendly approach. However, for saccharification of IL pretreated LB, IL stable enzymes must be used else the latter may be inhibited. Furthermore, availability of IL stable enzymes may help designing novel consolidated process by in situ coupling of IL mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…In another study, pine needle biomass was pretreated using IL followed by fermentation using S. cerevisiae and P. stipitis in a CBP system. The ethanol yield of 0.148 g/g was obtained after 72 h, and the fermentation efficiency of system was found at 41.39% (Vaid et al, 2018). Recently, recombinant S. cerevisiae ER T12 and M2n T1 strains (harboring integrated temA and temG Opt gene cassettes) simultaneously expressing αamylase and glucoamylase, produced 89.35 g/L and 98.13 g/L ethanol from starchy biomass in a single step CBP system at 30℃ after 192 h with carbon conversion of 87% and 94%, respectively (Cripwell et al, 2019).…”
Section: Consolidated Bioprocessing (Cbp)mentioning
confidence: 96%
“…In another study, pine needle biomass was pretreated using IL followed by fermentation using S. cerevisiae and P. stipitis in a CBP system. The ethanol yield of 0.148 g/g was obtained after 72 h, and the fermentation efficiency of system was found at 41.39% (Vaid et al, 2018). Recently, recombinant S. cerevisiae ER T12 and M2n T1 strains (harboring integrated temA and temG Opt gene cassettes) simultaneously expressing αamylase and glucoamylase, produced 89.35 g/L and 98.13 g/L ethanol from starchy biomass in a single step CBP system at 30℃ after 192 h with carbon conversion of 87% and 94%, respectively (Cripwell et al, 2019).…”
Section: Consolidated Bioprocessing (Cbp)mentioning
confidence: 96%
“…Recently, a study (Cunha et al, 2020) reported the use of engineered industrial Saccharomyces cerevisiae strains (whole-cell biocatalysts) as a promising commercial enzymatic cocktail for the production of ethanol from corn cob biomass. Other authors have also documented a one-pot CBP as a potential means for techno-economic feasibility of lignocellulosic-bioethanol-fuel production (Vaid et al, 2018). The authors optimized bioethanol production from pine needle biomass via single pot in-situ ionic liquid-based pretreatment and enzymatic saccharification.…”
Section: Fermentation Strategiesmentioning
confidence: 99%
“…Consolidated processing, a bio-manufacturing concept, was first implemented in the field of bio-fuel preparation from cellulose and lignin. 95 The industrial yeast strains with high enzyme activity and strong adverse environment tolerance are used to integrate fermentation enzyme production, cellulase hydrolysis and sugar fermentation in one reaction system, where agricultural/industrial by-products are used as raw materials to produce ethanol. Mushroom by-products are rich in fiber components, especially SMS, which is mainly composed of lignin similar to straw, sawdust, and corncob.…”
Section: Biological Energymentioning
confidence: 99%